Recommendations for assessing patient-reported outcomes and health-related quality of life in patients with urticaria: a GA2LEN taskforce position paper - Baiardini, I. (2011)
The aim of this Global Allergy and Asthma European Network (GA2LEN) consensus report is to provide recommendations and suggestions for assessing patient-reported outcomes (PROs) including health-related quality of life in patients with urticaria. We recommend that PROs should be used both in clinical trials and routine practice for the evaluation of urticaria patients. We suggest that PROs should be considered as the primary outcome of future clinical trials. Two validated and disease-specific instruments for assessing PROs are available, the urticaria activity score (for symptoms) and the chronic urticaria questionnaire on quality of life CU-Q2oL. This latter tool, CU-Q2oL, is available in many languages and should be preferred, where available, over more generic instruments for assessing urticaria-specific effects on quality of life. CU-Q2oL is only suited for the investigation of patients with chronic spontaneous urticaria. Similar instruments for other forms of urticaria have yet to be developed and validated. Also, tools for assessing other chronic spontaneous urticaria PROs besides quality of life and symptoms are needed.